Social Media Use in Developing English Speaking Skill among Vocational High School Students - Dwi Wijayanti; Junaedi Setiyono; Ismawati Ike Nugraeni (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
English speaking ability is a crucial skill in foreign language learning, yet many students still struggle to develop fluency and confidence. With today's technological advancements, social media has emerged as a potential tool to support more interactive and flexible language learning. This study aimed to investigate students' perceptions of the use of social media in improving their English speaking skills. A quantitative survey approach was used, involving 30 students at SMK N 1 Purworejo. Data were collected through a structured questionnaire and analyzed using descriptive statistics to obtain average scores for each indicator. The results showed that social media had a positive effect on students' confidence and comfort in speaking, with scores of 3.06 for both indicators. Furthermore, interactive features such as video calls, voice messages, and online discussions were considered effective in improving speaking fluency, with average scores ranging from 3.1 to 3.3. The results also indicated that students generally had positive perceptions of the use of social media in speaking learning, although some reported experiencing social pressure. This study highlights the potential of social media as an alternative tool to support the development of speaking skills through flexible and interactive learning. However, this study was limited by its small sample size and the use of self-reported data. Therefore, further research involving a larger population and incorporating data-driven assessments is recommended.